Effect of Micro-silica and Crumb Rubber on Mechanical Properties of Concrete - Dhiraj Agrawal; U P Waghe; M D Goel; Ashutosh Bagde (Engineering Access, 2024)
Several researches conducted on rubberized concrete in the past but very few researchers explained the bonding effect of the waste tire rubber particles with different cementitious materials. In this research the effect of the fineness of the micro silica and its bonding with the rubber particles is studied. To check the influence of fractional replacement of cement using micro silica and discarded tire rubber as limited substitution of sand with providing pre-treatment to rubber particles, this experimental investigation has been conducted on concrete with varying percentage switch of cement using micro silica (SF), especially micro-silica was used in this study to exchange with cement by its weight. SF exchanged cement from 0% to 12% with an incremental ratio of 3%. Along with this, the sand was fractionally replaced using pretreated crumb rubber (CR) particles derived from end-of-life tires. The replacement ratio changed by 5% by the volume of sand, ranging from 0% to 20%. The pre-treatment process for CR was done using Sodium Hydroxide (NaOH) of 1 Molarity, for achieving good bonding between cementitious material paste and rubber particles. Distinct fresh and hydrated concrete properties were assessed and compared with normal concrete (NC) having 0% SF and 0% CR. 17 concrete mixtures in all, together with the control mix, were assessed in this study with varying amounts of SF and CR. The bonding structure and impermeability were enhanced by using SF in concrete with promising enhancement in mechanical strengths. Based on the outcomes obtained from this research, the optimal proportion for partial substitution of cement and sand by SF and CR was fixed for the desired grade of concrete to provide an innovative form of concrete to the construction industry.